Case reportUnsuspected Klinefelter syndrome mosaicism presenting as osteoporosis: a case report - Mithun, Raj; Ilangovan, Veerappan; Jomal, Mathew; Ramachandra, Rao; Palamalai, Swaminathan Rathinam; Singh, Negi Vir (Archives of Medical Science, 2006)
Hypogonadism secondary to genetic disorders like Klinefelter syndrome has been described as a cause of male osteoporosis, but the diagnosis is frequently missed or delayed because the clinical features are often subtle or at times normal. We report the case of a 25 year old male mosaicism Klinefelter syndrome lacking typical clinical features such as tall stature, gynaecomastia or low intelligence, whose sole presentation was low back ache due to diffuse osteoporosis involving the vertebra and pelvic bones. Bone loss is a minor characteristic of KS, while it is a distinctive feature of idiopathic hypogonadotrophic hypogonadism. There are only a few reported cases of Klinefelter mosaicism in which the sole presenting symptom complex was osteoporosis. The diagnosis is often missed or delayed because of the low index of suspicion that many health care professionals have toward genetic diagnoses in adults.